Wo liegt Ecuador? : Exil in einem unbekannten Land 1938 bis zum Ende der fünfziger Jahre - Kreuter, Maria-Luise (Reihe Dokumente, Texte, Materialien / Zentrum für Antisemitismusforschung der Technischen Universität Berlin, 1995)
"Valuable study of Jewish refugees in Ecuador emphasizes those who, unlike members of the intellectual and scientific community, escaped from Europe late and had fewer options for host countries. Sources include 40 volumes of Quito's Jewish newspaper, published and unpublished work by the refugees, and 50 extensive interviews. Concentrates on immigrants' professional and social acculturation; their contributions to Ecuador; their cultural, religious, and social organizations; and relations within the Jewish community, with gentile victims of the Nazi regime, and with the existing German colony"--Handbook of Latin American Studies, v. 58